"Srce postaja odporno kot kamen /---/" - Pirjevec, Marija (Slavistična revija, 2006)
The burnig of the Trieste Natioanl Home (July 13, 1920) has been depicted in Slovene literature by three authors: Srečko Kosovel, Boris Pahor, and Alojz Rebula. This important topic from the history of Trieste went through three important stylistic formations in modern Slovene literature, i.e., expressionism, neo-realism, and the contemporary essayistic marrative, in eachof the three cases with other nuances of personal style.
Keywords: Fascism; fažizem; Kosovel, Srečko; Narodni dom v Trstu; National home in Trieste; Pahor, Boris; Rebula, Alojz; Slovene literature; slovenska književnost; Treiste; Trst